Analisis Uji Regresi Linear Sederhana dalam Penelitian Pendidikan - Lestari, Vina; Angriani Lubis, Rina; Hairani Tbn, Reni; Zulpan, Zulpan; Arianto, Arianto (Indo Publishing, 2026)
This study aims to explore the use of simple linear regression in the educational context, particularly in evaluating the effect of a single independent variable on a single dependent variable, such as the relationship between learning motivation and students’ academic achievement. The approach adopted is a literature study by examining various scientific references, including journals, books, and research articles related to simple linear regression. The findings indicate that simple linear regression plays an important role in education for measuring, predicting, and understanding quantitative interactions between variables. This method assists educators and researchers in identifying factors that significantly influence learning outcomes and in assessing the effectiveness of information-based learning programs. Moreover, simple linear regression offers advantages such as ease of analysis, predictive capability, and flexibility in its application across diverse educational contexts. This study emphasizes that simple linear regression is a fundamental and efficient method for educational analysis and can serve as a basis for further studies using more complex statistical models.